Correctional Policy and Overcapacity: Alternative Models for Reducing Prison Overcrowding - Nur Hidayah; Intan Triningsih (AT-TAFAHUM: Journal of Law, 2023)
The problem of overcrowding in correctional institutions in Indonesia is a structural issue closely related to the criminal law paradigm, which is still oriented towards imprisonment. Data shows that the number of prison inmates has reached almost twice the ideal capacity, thus disrupting the correctional function, increasing the risk of human rights violations, and decreasing the effectiveness of rehabilitation and social reintegration of prisoners. This study aims to analyze the root causes of overcrowding, evaluate the existing correctional policies, and offer alternative models based on restorative justice and non-imprisonment. Using qualitative methods through a normative juridical approach and policy analysis, this study examines laws and regulations, correctional statistics, and previous research findings. The results show that overcrowding is caused by the dominance of imprisonment, the minimal application of alternative punishments, the imbalance in the officer-to-inmate ratio, and weak coordination between law enforcement agencies. The implementation of restorative justice, supervised criminal justice, social work, and community-based rehabilitation has proven to have significant potential in reducing the number of prison inmates in a sustainable manner. This study recommends reform of correctional policy through the expansion of alternative sentencing options, strengthening institutional capacity, and digitalizing the correctional system as an effort to create a more humane, efficient, and equitable correctional system.